2006
DOI: 10.3201/eid1210.060102
|View full text |Cite
|
Sign up to set email alerts
|

Helminth-related Eosinophilia in African Immigrants, Gran Canaria

Abstract: Of 788 recent African adult immigrants to Las Palmas de Gran Canaria, 213 (27.0%) had eosinophilia. The most frequent causes were filariasis (29.4%), schistosomiasis (17.2%), and hookworm infection (16.8%). Stool microscopy and filarial and schistosomal serologic tests gave the highest diagnostic yield. Country of origin and eosinophil count were associated with specific diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
1
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 14 publications
2
40
1
13
Order By: Relevance
“…10,11,18,32 Similar to previous studies, no relationship was found between having symptoms and the presence of imported infectious diseases, suggesting that screening protocols should be carried out regardless of clinical status. 9,33 The prevalence of pathogenic infectious disease was high (73%).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…10,11,18,32 Similar to previous studies, no relationship was found between having symptoms and the presence of imported infectious diseases, suggesting that screening protocols should be carried out regardless of clinical status. 9,33 The prevalence of pathogenic infectious disease was high (73%).…”
Section: Discussionsupporting
confidence: 66%
“…16,17 Previous studies have considered relative and absolute eosinophilia and hyper-IgE as good indicators to facilitate the diagnosis of helminth infections in immigrants and travelers. [18][19][20][21] Some countries have launched screening protocols for immigrants including clinical history, physical examination, and laboratory screening. [22][23][24] This situation may be exacerbated by administrative problems such as the lack of legal documentation, difficulties to obtaining access to health care, and the attitude of not seeking medical treatment held by many immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Strongyloides was found in only 2.3%, but stool testing alone was performed (15). The country of origin was associated with specific diseases, and higher eosinophilic counts (median 1000×10 9 μL) were seen with filariasis (15). A Spanish study by Roca et al (16) found 200 cases (15.2%) of schistosomiasis among 1321 African immigrants, almost 50% of whom were asymptomatic and 30% had nonspecific abdominal pain.…”
mentioning
confidence: 99%
“…A parasitic infection was diagnosed in 75.6%, most frequently filariasis (29.6%) followed by schistosomiasis (17.4%), hookworm infection (16.8%) and Trichuris species (8.4%) infection. Strongyloides was found in only 2.3%, but stool testing alone was performed (15). The country of origin was associated with specific diseases, and higher eosinophilic counts (median 1000×10 9 μL) were seen with filariasis (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation